Assessing the impact of teaching ethics - Sojka, Jane Z.; Gupta, Ashok K.; Nandola, Kahandas (Marketing & Menedzsment, 2019)
Although the inclusion of ethics in the business curriculum is becoming increasingly important, little is known about the impact classroom discussions of ethics has had on student awareness of ethical issues. Using both self-assessment and objective assessment measures, this research found that students who had been exposed to ethics in business classes considered themselves more knowledgeable about ethics and reported a higher confidence in their ability to make ethical decisions than students who had less exposure to ethics in the classroom. In addition, students with increased classroom exposure to ethics were also found to have greater awareness of ethical issues in both business situations and consumer situations: suggesting that including ethics in the business curriculum is having a positive impact. Areas for future research on this topic are suggested.